The Toyota product development system : integrating people, process, and technology - Morgan, James M.; Liker, Jeffrey K. (New York : Productivity Press, 2006)
The ability to bring new and innovative products to market rapidly is the prime critical competence for any successful consumer-driven company. This book examines and analyzes the truly effective product development methodology that has made Toyota the most forward-thinking company in the automotive industry
1. Introduction -- 2. Process subsystem -- 3. People subsystem -- 4. Tools and technology subsystem -- 5. Creating a coherent lean PD system
Includes bibliographical references (p. 359-363) and index
Keywords: Automobiles -- Design and construction; Concurrent engineering; Project management